2018
DOI: 10.1111/aos.13909
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids exert differential effects on the endothelium in an in vitro model of the blood–retinal barrier

Abstract: Glucocorticoids have differential effects in an experimental in vitro BRB model. TA is the most potent in improving barrier function, both at the molecular and functional levels, and TA prevents VEGF-induced expression of PLVAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…A positive correlation was registered between differential light sensitivity and the cumulative dose of corticosteroids in our study population, supporting a potential protective role of steroids in maintaining retinal function in course of a systemic inflammatory disease [41]. However, it should be noted that perimetric indices of visual field can be affected by the significant ocular discomfort of PsA patients, in accordance with the literature reporting that the better tear film stability the higher optical quality of the anterior corneal surface [41]. Published studies showed that dry corneal surfaces can certainly affect the SAP findings [42][43][44].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A positive correlation was registered between differential light sensitivity and the cumulative dose of corticosteroids in our study population, supporting a potential protective role of steroids in maintaining retinal function in course of a systemic inflammatory disease [41]. However, it should be noted that perimetric indices of visual field can be affected by the significant ocular discomfort of PsA patients, in accordance with the literature reporting that the better tear film stability the higher optical quality of the anterior corneal surface [41]. Published studies showed that dry corneal surfaces can certainly affect the SAP findings [42][43][44].…”
Section: Discussionsupporting
confidence: 77%
“…Since no correlation between age and the retinal sensitivity was observed in controls, it is likely that, in PsA patients, the abnormal retinal sensitivity function can be related to a potential damage in retinal structures detectable in chronic diseases [37,40]. A positive correlation was registered between differential light sensitivity and the cumulative dose of corticosteroids in our study population, supporting a potential protective role of steroids in maintaining retinal function in course of a systemic inflammatory disease [41]. However, it should be noted that perimetric indices of visual field can be affected by the significant ocular discomfort of PsA patients, in accordance with the literature reporting that the better tear film stability the higher optical quality of the anterior corneal surface [41].…”
Section: Discussionmentioning
confidence: 49%
“…In the present study, ALD and HC significantly increased the gene expression of ZO-1 , coding a well-known tight junction-associated protein and adherens junction protein, which could affect the Na-F transport. A previous report demonstrated increased expression of ZO-1, occludin, and claudin-5 by glucocorticoids in primary bovine retinal endothelial cells 29 . Although immunohistochemistry did not reflect the increased gene expression of ZO-1 in this study, the integrity of the tight junction is an important factor in paracellular transport.…”
Section: Discussionmentioning
confidence: 80%
“…In general, out of 128 OEMR patients, on whom information on radiation was available, only a minority of 17 patients (13%) received local irradiation (n = 15) or local radiation combined with TBI (n = 2) whereas the majority did not (Supplementary Table S2). As an exception, relapses within the eye have been considered as specific local risk being potentially protected from chemotherapeutic agents by a blood-retina barrier [35]. Three out of four patients with ocular relapses received irradiation of the eye.…”
Section: Oemr Shows a Distinct Event Pattern Compared To Non-oemrmentioning
confidence: 99%